Wardlaw's contemporary nutrition - Smith, Anne M., 1955-; Collene, Angela; Spees, Colleen K.; Wardlaw, Gordon M. (New York : McGraw-Hill Education, 2022)
"Wardlaw's Contemporary Nutrition is designed to accurately convey changing and seemingly conflicting messages to all kinds of students. Our students commonly have misconceptions about nutrition, and many have a limited background in biology or chemistry. We teach complex scientific concepts at a level that will enable you to apply the material to your own life. This marks the eleventh edition of Wardlaw's Contemporary Nutrition. We are very excited to introduce you to our newest author, Dr. Colleen Spees! Like our other authors, she is a Registered Dietitian Nutritionist, which means she will help you to translate nutrition science into practical advice. At The Ohio State University, Dr. Spees is a valued expert on cancer, nutritional genomics, and food security. We are thrilled to add her unique perspective and contemporary ideas. As in previous editions, we have written this book to help you make informed choices about the food you eat. We will take you through explanations of the nutrients in food and their relationship to health and make you aware of the multitude of other factors that drive food choices. To guide you, we refer to many reputable research studies, books, policies, and websites throughout the book. With this information at your fingertips, you will be well equipped to make your own informed choices about what and how much to eat. There is much to learn, so let's get started!"--
Part 1: Nutrition : a key to health. Nutrition, food choices, and health ; Designing a healthy eating pattern ; The human body : a nutrition perspective -- Part 2: Energy nutrients and energy balance. Carbohydrates ; Lipids ; Proteins ; Energy balance -- Part 3: Vitamins, minerals, and water. Vitamins and phytochemicals ; Water and minerals -- Part 4: Nutrition : beyond the nutrients. Nutrition : fitness and sports ; Eating disorders ; Protecting our food supply ; Global nutrition -- Part 5: Nutrition : a focus on life stages. Nutrition during pregnancy and breastfeeding ; Nutrition from infancy through adolescence ; Nutrition during adulthood -- Appendix A: Daily values used on food labels -- Appendix B: Diabetes menu-planning tools -- Appendix C: Dietary assessment -- Appendix D: Chemical structures important in nutrition -- Appendix E: Sources of nutrition information -- Appendix F: English-metric conversions and metric units -- Appendix G: DRI tables -- Glossary.
Includes bibliographical references and index.
Keywords: Nutrition; Textbooks; Textbooks